2015
DOI: 10.1007/s12149-015-1036-9
|View full text |Cite
|
Sign up to set email alerts
|

The edge artifact in the point-spread function-based PET reconstruction at different sphere-to-background ratios of radioactivity

Abstract: The edge artifacts in the PET images reconstructed using the PSF algorithm increased with an increasing SBR. In the small spheres, the edge artifact was observed as a sharp peak at the center of spheres and could result in overestimation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 20 publications
2
12
0
2
Order By: Relevance
“…Kidera et al reported that the PSF model resulted in the greatest increase in contrast RC for 13-mm hot spheres. Spheres between 10 and 17 mm showed improvement in contrast RC, whereas no such improvement was noted for larger spheres (22). Our results also showed that PSF correction increased the DI in spheres 8 mm or larger but not in spheres smaller than 8 mm.…”
Section: Discussionsupporting
confidence: 62%
“…Kidera et al reported that the PSF model resulted in the greatest increase in contrast RC for 13-mm hot spheres. Spheres between 10 and 17 mm showed improvement in contrast RC, whereas no such improvement was noted for larger spheres (22). Our results also showed that PSF correction increased the DI in spheres 8 mm or larger but not in spheres smaller than 8 mm.…”
Section: Discussionsupporting
confidence: 62%
“…PSF correction has been reported to result in overestimation due to edge artifacts in small regions and is therefore a problem for quantification (25). We previously reported that edge artifacts were observed as a sharp peak at the center of small hot spheres (26). Zhang et al found that edge artifacts were unclear in areas of low radioactivity (27).…”
Section: Discussionmentioning
confidence: 97%
“…1) [24]. Allerdings wurde für diese PSF-Rekonstruktionen auch gezeigt, dass typische Randwert-Überschätzungen (Gibson-Artefakte) auftreten können, was bei quantitativen Betrachtungen zu Problemen führen kann [25,26].…”
Section: Algorithmenunclassified